Assembling Discovery Learning Model of Learning to Increase Activity and Results of Learning Geography in Class X Mipa 1 SMAN 3 Padang Panjang - Zulhendri, Zulhendri; Anwar, Syafri (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Discovery method is a component of educational practices that include teaching methods that promote active learning, the orientation in process, directing his own, find your own and reflective, Use of discovery learning, wants to change the conditions of passive learning to active and creative, learning teacher oriented to student oriented, and change the ekspository mode students only receive information from the student's teacher Discovery mode to find information themselves. The learning result is the ability of the students after receiving a learning experience. With action research methods class through two cycles of data obtained an increase in the results of class X MIPA 1 SMAN 3 Padang Panjang, amounting to 29 students from the mean value approximately 52% of students scoring above the clasical minimal value, and 48% of students are below the clasical minimal value, bethe average value approximately 86% of students scoring above the clasical minimal value, and 14% of students are below the clasical minimal value, learning discovery in learning geography will increase the activity of students in learning, both of individually and classical. Increased activity of students in learning makes students more enthusiastic about learning and will improve student learning outcomes.